Trends and diversity of Japanese encephalitis videos on YouTube: an analysis of Indonesian-language health promotion content - Najiyati, Ifa; Maysarah, Amalia; Muqarohmah, Nia Lestari; Kusumaningrum, Fitrina Mahardani; Firdaus, Amalia; Yulyana, Yana; Ramadona, Aditya Lia (BKM Public Health and Community Medicine, 2025)
Purpose: This study aims to analyze trends and diversity in Japanese encephalitis videos on YouTube to promote health information in Indonesia. Methods: We collected the videos on YouTube by searching with the keyword “Japanese encephalitis”. The search results were identified to confirm their relevance to Japanese Encephalitis, and the videos were then classified for use in Indonesia. We analyze trends by examining the frequency of videos over time. For the videos identified as Indonesian-language content, further categorization was conducted based on their thematic content type. Results: We retrieved 586 videos and excluded 44 videos that were not related to Japanese encephalitis. The videos were published from January 6, 2008, to August 3, 2024. There was a global increase in the production of Japanese encephalitis content videos on YouTube, particularly in 2019, from 3.5% to 11.4%. However, only 22 (4.31%) Japanese encephalitis-related videos used Indonesian, with the most common content category being educational (22.7%). Conclusion: An increase in Japanese encephalitis-related content videos on YouTube in 2019, yet Indonesian-language videos remain limited. This highlights the need for more Indonesian-language content and more diverse information on Japanese encephalitis, targeted to Indonesian audiences, to improve public awareness and preventive measures.